2016
DOI: 10.1177/0022427816645380
|View full text |Cite
|
Sign up to set email alerts
|

Educational Pathways and Change in Crime Between Adolescence and Early Adulthood

Abstract: Objectives This article examines the relationship between intergenerational educational pathways and change in crime. Moreover, it examines the potential mediating roles of family and employment transitions, economic stressors, and social psychological factors. Method Data from the National Longitudinal Study of Adolescent to Adult Health (N = 14,742) and negative binomial models are used to assess associations between educational pathways (i.e., upward, downward, and stable) and change in crime between adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
(116 reference statements)
0
12
1
2
Order By: Relevance
“…Regarding the multidimensional nature of risk factors for engaging in crime, as suggested by previous studies, sociodemographic (especially gender and age) ( 64 ), education ( 65 ), and economic factors (such as socioeconomic status) ( 12 ) were determinants of the incidence of crime. In Western populations, the association between age and crime mainly follows a bell-shaped pattern, known as the age-of-crime curve, showing a reduction in criminal activity as an individual progress into adulthood ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Regarding the multidimensional nature of risk factors for engaging in crime, as suggested by previous studies, sociodemographic (especially gender and age) ( 64 ), education ( 65 ), and economic factors (such as socioeconomic status) ( 12 ) were determinants of the incidence of crime. In Western populations, the association between age and crime mainly follows a bell-shaped pattern, known as the age-of-crime curve, showing a reduction in criminal activity as an individual progress into adulthood ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, earlier studies have shown that education may counteract the risk of committing crimes, being that those with a higher level of education have higher expectations regarding the amount of income they can derived from legal ventures ( 65 ). Moreover, the inverse relationship between social stratification and delinquency turns out to be one of the main points of interest in criminology ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors, after only observing minor evidence of mobility being associated with felony arrest at the bivariate level, concluded that they found little support for the hypothesized relationship between educational mobility and crime (Savolainen et al, 2014). Another recent example is by Swisher and Dennison (2016) who found upward mobility to be associated with decreases in crime and downward mobility to be associated with increases in crime using a nationally representative sample from the United States.…”
Section: Educational Mobility and Crimementioning
confidence: 99%
“…The socioeconomic differences previously discussed are the crux of why intergenerational mobility may produce variation in crime by race and ethnicity. From the perspective of social mobility, upward educational trajectories have been found to be associated with decreases in crime (Swisher & Dennison, 2016). Therefore, if Blacks and Hispanics are more likely to be exposed to cumulative disadvantage across the life course (Sampson & Laub, 1997), then the benefits of pursuing higher education may be more meaningful compared to Whites (Swisher, Kuhl, & Chavez, 2013).…”
Section: Race Ethnicity and The Mobility And Crime Relationshipmentioning
confidence: 99%
See 1 more Smart Citation